Medientechnologie und Affekt Kameras, ihre Anwendung und die Poetik des Irakkriegsfilms - Pogodda, Cilli (Cinepoetics, 2022)
The fact that media technologies influence our feelings seems obvious. But how do digital cameras or MP3 players change how we perceive, feel, and emotionally assess the world? This book examines the connection between media technology and affect on the level of the poetic patterns of audiovisual images, combining rigorous methods of film analysis with praxeological and genre-theoretical approaches.